The effect of different crossing angles on similarity and stability of target spectra in Forward Scattering Micro Radar (FSMR) using graphical user interface (GUI) / Hanis Adiba Mohamad - Mohamad, Hanis Adiba (2012)
This paper investigates the effect of different crossing angles of target spectra in Forward Scattering Micro Radar (FSMR). Target modeling and simulation signals have been executed using MATLAB Software to evaluate the performance of ground based Forward Scattering Radar (FSR) with omnidirectional antennas that operates at a low frequency bands (VHF and UHF). The obtained results show the effect of different crossing angles to the target spectra.